A Comparative Phytochemical Profiling of Cassia tora Linn. - A. BHALERAO, SATISH (Asian Journal of Chemistry, 2010)
Cassia tora Linn. (Family: Leguminosae, Sub-family: Caesalpinaceae) locally known as Takala, a herb that grows abundantly during the rainy season is an edible plant when in juvenile condition and is consumed as a vegetable. But the plant losses edibility after maturity i.e. when it bears flowers and fruits. It is also observed that cattle which usually eat this plant when it is young, avoid it after maturation. The possible reason for the loss of this edibility is the accumulation of metabolites that are toxic to human beings and work as anti-feedants or as agents of anti-herbivory in cattle. Present paper is based on the comparative estimation and profiling of the young and mature plants by HPTLC analysis method. The purpose of present study is to find out the possible anti-feedant agents if any, in the mature plant. It has been observed that total flavonoid content of the mature plant is remarkably high as compared to the young plants. These flavonoids might be responsible for the anti-feedant potential.